2020
DOI: 10.5114/pg.2020.98538
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between IL-6 and thrombocytosis accompanying gastrointestinal tumours

Abstract: Introduction Several reports have stated that thrombocytosis is associated with worse survival and higher rate of metastasis in solid tumours. A study in ovarian tumours implicated IL-6 produced by tumour cells as a key mechanistic factor. Aim To evaluate the relevance of this paraneoplastic pathway in gastrointestinal cancer. Material and methods After excluding thromboembolic and inflammatory disorders, 161 patients were enrolled who had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In people, gastrointestinal carcinomas are commonly associated with thrombocytosis, and in certain tumor types, such as colorectal carcinoma, thrombocytosis is a negative prognostic indicator. 23 25 Carcinoma was an uncommon diagnosis in this study, but gastrointestinal lymphoma as well as gastrointestinal inflammatory diseases were more frequently diagnosed in cats with thrombocytosis when compared with the control group. Gastrointestinal carcinoma tumor cells have been shown to produce IL-6, which, in turn, increases thrombopoiesis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In people, gastrointestinal carcinomas are commonly associated with thrombocytosis, and in certain tumor types, such as colorectal carcinoma, thrombocytosis is a negative prognostic indicator. 23 25 Carcinoma was an uncommon diagnosis in this study, but gastrointestinal lymphoma as well as gastrointestinal inflammatory diseases were more frequently diagnosed in cats with thrombocytosis when compared with the control group. Gastrointestinal carcinoma tumor cells have been shown to produce IL-6, which, in turn, increases thrombopoiesis.…”
Section: Discussionmentioning
confidence: 58%
“…Gastrointestinal carcinoma tumor cells have been shown to produce IL-6, which, in turn, increases thrombopoiesis. 25 It is not known if tumor cells in feline lymphoma directly produce IL-6 as a paraneoplastic mechanism, but IL-6 may be produced as part of the inflammatory milieu of the tumor’s chronic clinical progression, especially in virus-associated feline lymphoma. 13 , 26 28 Feline small intestinal lymphoma has a T-cell predominant phenotype and is associated with chronic inflammatory and neoplastic changes to the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study [ 20 ], we have reported that a personalized, relative platelet measure can predict disease outcome significantly better than “traditional” thrombocytosis, which further strengthened that the definition of thrombocytosis needs to be revised. The biochemical detection of paraneoplastic thrombocytosis in CRC is a novel research area [ 36 ]. In the current study, we observed higher interleukin-6 and thrombopoietin levels of CRC patients, compared to those of control subjects, supporting the presence of paraneoplastic thrombocytosis, which was further strengthened by the result of correlation and survival analysis, in line with earlier findings [ 1 , 2 , 31 , 32 , 33 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical detection of paraneoplastic thrombocytosis in CRC is a novel research area [ 36 ]. In the current study, we observed higher interleukin-6 and thrombopoietin levels of CRC patients, compared to those of control subjects, supporting the presence of paraneoplastic thrombocytosis, which was further strengthened by the result of correlation and survival analysis, in line with earlier findings [ 1 , 2 , 31 , 32 , 33 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular mechanisms have been suggested to underlie the progression of cancer-associated thrombocytosis, which involves various tumor-associated cytokines and humoral factors directly or indirectly affecting megakaryopoiesis and thrombopoiesis during cancer development [19]. These factors notably include granulocyte-macrophage colony-stimulating factor (GM-CSF), granulocyte colony-stimulating factor (G-CSF), thrombopoietin (TPO), interleukin-6 (IL-6), vascular endothelial growth factor (VEGF), basic fibroblast growth factor (b-FGF), and interleukin-1 (IL-1) [20]. Primary tumors secrete G-CSF and GM-CSF, which stimulate megakaryopoiesis in an endocrine manner and induce thrombopoiesis in people with cancer.…”
Section: Thrombocytosis and Cancermentioning
confidence: 99%